Free Boundaries Problem for a Class of Parabolic Type Chemotaxis Model (Journal of Partial Differential Equations, 2023)
In this paper, we are interested in a free boundary problem for a chemotaxis model with double free boundaries. We use contraction mapping principle andoperator-theoretic approach to establish local solvability of a chemotaxis system in 1-Dimensional domain with non-constant coefficient free boundaries.
Keywords: Free boundary; chemotaxis; local solution.